A Narrative and Meta‑Analytic Study of in vivo Efficiency of the Bioactive Compounds of Propolis in Tooth Decay - Kim, Yun Jin; Yong, Yean Kong; Aslam, Muhammad Shahzad (Pharmacognosy Reviews)
Background: Propolis is one of the major components produced by honeybee. It is well known in different parts of the world such as Iran, Canada, Yemen, Czech Republic, Ethiopia, Bulgaria, Portugal, India, Turkey, Malaysia, the United States of America, Chile, Brazil, and Indonesia. The bioactive constituent of every type of propolis varies depending on the geographical location. Terpenoids, flavonoids, and polyphenol compounds were found to be common in all kinds of propolis. It possess numerous applications such as control of dental infections, plaque clean ing, treating gingivitis, exhibiting antimicrobial effect and treating radiation-induced oral mucositis and cariogenic infections in caries-active patients. Methodology: This study thus aimed to undertake a meta-analysis of the efficacy of bioactive compounds of propolis in tooth decay. A total of three in vivo studies were systematically reviewed, and two studies with a total of 300 pathogen-free female Wistar rats were included in the final meta-analysis. Results: The results were compared among three subcategories of smooth surface caries and sulcal caries;(slight, moderate, and severe), supporting a statistically significant(P;=0.006) beneficial effect of using fractional propolis. Conclusion: Most of the included studies were preliminary, without blind study and lack of information about standard animal housing protocol. More in vivo and clinical trials of bioactive compounds of propolis should be encouraged in future.
Keywords: Dental hygiene; in vivo studies; meta-analysis; propolis; tooth decay; traditional medicine